The entrepreneurial dilemma in the life cycle of the small firm : how the firm and the entrepreneur change during the life cycle of the firm, or how they should change - Masurel, Enno, 1959- (Bingley, U.K. : Emerald Publishing Limited, 2019)
Entrepreneurial dilemmas play an important, though heavily underexposed, role in the life cycle of the small firm. This book defines the entrepreneurial dilemma as a situation where entrepreneurs have to choose between multiple future courses of action concerning their firm, without sufficient information to make that choice. The Entrepreneurial Dilemma within the Life Cycle of the Small Firm enables lecturers, researchers and practitioners in the fields of entrepreneurship, small business development and business administration to understand these entrepreneurial dilemmas and ways to resolve them. This book presents an in-depth analysis of the modern theories in the field of entrepreneurship, including innovation, sustainable entrepreneurship, characteristics of small businesses, the life cycle of the firm, entrepreneurial behavior and small business finance. Enno Masurel provides a clear overview of the opportunities that teaching entrepreneurship in a higher education context offers, and embodies this teaching within ten universal cases that will help readers to further understand the the dilemmas faced by entrepreneurial activity in the development of small firms.
Prelims -- Introduction -- Theoretical background of entrepreneurship -- Entrepreneurship education -- Cases about the entrepreneurial dilemma in the development of the small firm -- Appendix 1: The financial plan -- Appendix 2: Case - the financial plan of Pizza Pete -- Appendix 3: Business model canvas 2018 -- Appendix 4: Lean start-up in a nutshell -- Appendix 5: Sustainable entrepreneurship balanced scorecard -- Index.
Includes index.
Print version record
Keywords: Entrepreneurship; Small business -- Growth; Organizational change; Sustainable development; Business & Economics -- Entrepreneurship; Economics, finance, business & management